Literatur Review : Pengaruh Artificial Intelligence (AI) Terhadap Motivasi Belajar Siswa: Penelitian - Zahwa Ardhy Nur'aeni; Mei Riski; Arsyida Diva Salsabila; Didik Tri Setiyoko (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Artificial intelligence (AI) is a prime example of the rapid development of modern technology. Education is one of the many fields impacted by AI. Student learning motivation, which is a crucial component in the learning process and is influenced by a number of factors, is crucial for the effectiveness of teaching and learning activities. This study aims to investigate the relationship between student learning motivation and the use of AI. The research methodology involved examining the literature using the Google Scholar database. The following inclusion criteria were used to screen the articles: 1) Selecting search terms such as "learning motivation," "artificial intelligence," and "students"; 2) Selecting literature based on source quality, year of publication, and topic relevance; 3) Reading each article and noting its main conclusions. The results of the study indicate that AI-based teaching and learning activities can produce inventive and engaging learning experiences, which in turn increase students' desire to learn.